Monoacylglycerols as fruit juices preservatives - Iva DOLEŽÁLKOVÁ; Zdeněk MÁČALÍK; Adéla BUTKOVIČOVÁ; Rahula JANIŠ; Leona BUŇKOVÁ (Czech Journal of Food Sciences, 2012)
Limiting or preventing the growth of undesirable microbial flora in food products is one of the main goals of food microbiology. A number of preservation methods have been designed to extend the shelf-life of the food products by reducing the microbial growth while new antimicrobials are still examined. Monoglycerides are naturally occurring compounds with inhibitory activity against various microorganisms. We evaluate the antimicrobial effects of 8 monoglycerides in vitro and in fresh unpasteurised apple juice. Out of all monoglycerides tested, monocaprin (MAG C10:0) and monolaurin (MAG C12:0) showed the best ability to supress or prevent the growth of filamentous fungi in vitro. The addition of these monoglycerides to apple juice resulted in a decrease in total viable counts of bacteria and yeasts. Monocaprin was able to stop completely the growth of bacteria and yeasts at a concentration of 250 µg/ml, and to prevent microbial spoilage of apple juices for at least two weeks.